Factors affecting pre-concentration of tocopherols and tocotrienols from palm fatty acid distillate by lipase-catalysed hydrolysis - Chu, B.S.; Baharin, B.S.; Quek, S.Y. (Elsevier, 2002)
Vitamin E in palm fatty acid distillate (PFAD) was pre-concentrated using an enzymatic hydrolysis-neutralisation method. Acylglycerols in PFAD was hydrolysed using a commercial immobilised thermal-stable Candida antarctica lipase (Novozyme 435 lipase) to liberate free fatty acids (FFA) and subsequently treated with an alkali. Removal of the FFA salts resulted in concentration of vitamin E. Factors affecting the degree of hydrolysis were studied to reach better understanding of the recovery of vitamin E from PFAD. Results showed that hydrolysis of 1:1 (w/v) ratio of PFAD and water mixture achieved its equilibrium after 5 h of reaction at 65±1 °C. The FFA levels in PFAD increased from initially 85 to about 97% at the equilibrium, while concentration of the vitamin E extracted increased from 1–7% to 7–1%. The FFA levels in PFAD remained unchanged but vitamin E concentration decreased when the reaction was prolonged to 7 h. The vitamin might have been oxidised due to the long period of heating at 65 °C. Increase of water content in the reaction mixture from 20 to 50% w/v increased both the FFA and vitamin E significantly (P<0.05). However, further increments of water content in the mixture significantly (P<0.05) decreased the FFA levels and vitamin E concentration. The optimum lipase concentration for the hydrolysis was about 1.0–1.5% w/w, whereby the FFA levels could be increased to approximately 94%. Meanwhile, the optimum temperature of the lipase was about 70 °C and the maximum FFA and vitamin E levels were 97% and 7–8%, respectively. When the reaction temperature was further increased from 70 to 85 °C, both the FFA and vitamin E levels decreased significantly (P<0.05). High temperature inactivated the lipase and promoted the oxidation of vitamin E. The interactions of these parameters during the hydrolysis can be optimised to achieve a maximum concentration of vitamin E.